Chronic Wound Caring Experience with Telehealth - Ni Ketut Kardiyudiani; Josephine Daquioag Lorica (Indonesian Journal of Global Health Research, 2021)
Chronic wounds are often associated with slow healing time, patients with chronic wounds will have an impact on physiological, psychological, social and financial burdens. The pandemic situation encourages the use of telehealth for wound care, so it is important to analyze it. To explore the experiences of patients with chronic wounds and receiving telehealth care. Materials and Methods: This research method is a meta-analysis with a qualitative approach. An article search was conducted on Google Scholar and Science Direct, entering the keywords "chronic wound patient experience with Telehealth" OR "telehealth wound care" and the second keyword entering the words "chronic wound experience", AND "telehealth wound care" AND "research qualitative" AND "chronic wound care experience with Telehealth". Found 1,085 articles from 2010-2020, then filtered according to the inclusion and exclusion criteria by referring to the prism protocol, so that 10 articles were extracted. This meta-analysis identified four overarching themes with 13 sub-themes. The four are wound knowledge, wound care technology, telehealth benefits, management systems. The use of telehealth in chronic wound care needs to pay attention to the four identified themes, to be able to provide wound care according to patient care needs